Impact of Glomerular Filtration Rate on Intravenous Thrombolytic Therapy in Acute Ischemic Stroke: A Retrospective Study from a Single Italian Center - Fabio Fabbian; Cristiano Azzini; Mauro Gentile; Alfredo De Giorgi; Alessandro De Vito; Francesco Portaluppi; Ilaria Casetta (Archives of Clinical Nephrology - Peertechz Publications, 2015)
Aim: Chronic kidney disease (CKD) is a risk factor for stroke and in-hospital mortality due to stroke. Stroke is highly prevalent in CKD patients. Our aim was to evaluate the impact of glomerular filtration rate in acute ischemic stroke (IS) patients after thrombolytic therapy.   Methods: All patients who underwent thrombolytic therapy for acute IS in our Department between 2009 and 2012 were studied retrospectively. Age, co-morbidities, blood pressure, glycaemia, National Institutes of health Stroke Scale score were evaluated. Renal function was estimated by CKD-EPI equation. Three-month outcome (death, residual disability, intracranial hemorrhage) in patients with glomerular filtration rate (GFR) <60 ml/min/1.73m2 was compared to that of patients with GFR ≥ 60 ml/min/1.73 m2. Logistic regression analysis was used to determine which factor was independently associated with outcome. Results: Among 191 patients treated for acute IS, 74 had GFR<60 ml/min/1.73m2. They were older and had higher prevalence of hypertension than patients with normal filtration rate. We found no differences in 3-month death or poor outcome between the two groups. However, patients with impaired renal function had a significantly higher risk of hemorrhagic complication (OR = 2.5; 95% CI = 1.1-6.2, p<0.01). Conclusion: GFR<60 ml/min/1.73m2 significantly affects the risk of intracranial hemorrhage in stroke patients treated with thrombolytic therapy. Hence, subjects with reduced renal function eligible for intravenous thrombolysis could be informed about the increased ICH risk.